The power of jus cogens in the shadow of procedural obstacles. Legal dilemmas in international cases concerning severe human rights violations, special regards to the Ukraine–Russia War - Takács, Izolda (Pedagogika Społeczna Nova, 2024)
Jurisdictional immunity of foreign states remains a rule under international law, even in cases involv- ing violations of peremptory norms of international law (jus cogens). Therefore, the assumption that the primacy view of jus cogens can resolve the dilemma over the relationship between serious human rights violations and state sovereignty is misleading and does not always prevail in practical applica- tion. This paper first outlines the “evergreen” dilemma of jus cogens versus state immunity, followed by an illustration of how procedural issues are addressed in pivotal international cases. In this regard, the paper primarily focuses on criminal proceedings submitted to the International Criminal Court (ICC) and the International Court of Justice (ICJ) to explore the issue more thoroughly. Finally, considering the unresolved nature of the central issue and the international climate, the study extends the nucleus of the problem to the ongoing Russia-Ukraine war.